Malice - Lord, Gabrielle (Conspiracy 365)
"Cal, Winter, Ryan and Boges have had enough adventures for a lifetime. Now all their enemies are locked up or have disappeared. Still, winter can't shake the feeling that she is being watched. When she's mailed a note say, The Drowner ... 30 days, her worst fears are realized. Who could be after her and her friends this time? With Cal away at flight school and a dangerous mystery to solve, will Winter be able to survive the 30-day countdown? Or will the Drowner live up to his name? The clock is ticking. Any second could be her last"--Publisher.